Socioeconomic Status, Health Inequalities, and Solidarity Trends in a Mass Vaccination Campaign. (13th November 2019) - Tur-Sinai, A; Gur-Arie, R; Davidovitch, N; Kopel, E; Glazer, Y; Anis, E; Grotto, I
Abstract: Background: In July 2013, Israel was swept with fear of a polio outbreak. In response to the importation of wild polio virus, the Ministry decided to take preventive action by administering oral poliovirus vaccine (OPV) to all children born after 1 January 2004 who had received at least one dose of inactivated poliovirus vaccine (IPV) in the past. This study analyzes the vaccination uptake rates resulting from the mass polio vaccination campaign on the basis of health inequality parameters of socioeconomic status (SES), principles of solidarity, and the Gini inequality index. The research explores understanding the value of the Gini inequality index within the context of SES and solidarity. Methods: The study is based on data gathered from the Israeli Ministry of Health's administrative records from mother-and-child clinics across Israel. The research population is comprised of resident infants and children whom the Ministry of Health defined as eligible for the OPV between August and December 2013. Results: The higher the SES level of the area where the mother-and-child clinic is located, the lower the OPV vaccination uptake is. The greater the income inequality is in the municipality where the mother-and-child clinic is situated, the lower the vaccination uptake. As time passed in the vaccination campaign, vaccination uptake increased regardless of the location of the mother-and-child clinics. The highest vaccination uptake rate was found among populations of low SES and low Gini inequality index. The lowest vaccination uptake rate was found among populations of high SES/high Gini inequality index. Conclusions: Public health professionals promoting vaccine programs need to make specially-designed efforts both in localities with high average income and in localities with a high level of income diversity/inequality. Such practice will better utilize funds, resources, and manpower dedicated to increasing vaccination uptake across varying populations and communities. Key messages: The higher the SES in municipalities with mother-and-child clinics, the less likely children were to be vaccinated. The lower the Gini inequality index, there is a higher polio vaccination uptake among of children.